A randomized controlled trial of standard vs customized graduated elastic compression stockings in patients with chronic venous disease - Yang, Wen-Tao; Xiong, Ying; Wang, Sheng-Xing; Ren, Hua-Liang; Gong, Chi; Jin, Zhen-Yi; Wen, Jia-Hao; Zhang, Wang-De; Tao, Xiao-Ming; Li, Chun-Min (Journal of vascular surgery. Venous and lymphatic disorders (New York, NY), 2024)
This study aimed to compare the efficacy of customized graduated elastic compression stockings (c-GECSs) based on lower leg parameter models with standard GECSs (s-GECSs) in patients with chronic venous disease (CVD). In this randomized, single-blind, controlled trial, 79 patients with stage C2 or C3 CVD were assigned to one of two groups: c-GECSs or s-GECSs. The primary outcome was change to Venous Insufficiency Epidemiological and Economic Study Quality of Life (VEINES-QOL) scores at months 1, 3, and 6 as compared with baseline. Secondary outcomes included compliance with wearing ECSs, interface pressure at the smallest circumference of the ankle (point B) and the largest circumference of the calf (point C), and calf volume (CV). There were 13 pairs of s-GECS and 2 pairs of c-GECS that showed pressure values higher than the standard at either point B or C. The c-GECSs were significantly superior to s-GECSs in terms of score improvement at all three time points (month 1, 8.47 [95% confidence interval (CI), 7.47-9.45] vs 5.89 [95% CI, 5.00-6.78]; month 3, 9.60 [95% CI, 8.47-10.72] vs 6.72 [95% CI, 5.62-7.83]; month 6, 7.09 [95% CI, 5.93-8.24] vs 3.92 [95% CI, 2.67-5.18]; P < .0001). Besides, at month 1, the mean daily use time of the c-GECS and s-GECS groups was 10.7 and 9.5 hours, respectively (P < .05). Correlation analysis indicated a negative relationship between local high pressure and daily duration in the s-GECS group (rpb = –0.388; n = 38; P < .05). Variances in pressure were greater in the s-GECSs group. The c-GECSs showed advantage in maintaining pressure. Both c-GECSs and s-GECSs effectively reduced CV (mL), with no significant differences between groups (month 1, 90.0 [95% CI, 71.4-108.5] vs 85.0 [95% CI, 65.6-104.2]; month 3, 93.8 [95% CI, 69.7-117.8] vs 85.9 [95% CI, 65.5-106.2]; month 6, 70.8 [95% CI, 46.5-95.2]) vs 60.8 [95% CI, 44.1-77.5]). The c-GECSs based on individual leg parameter models significantly improved VEINES-QOL scores and provided stable and enduring pressure as compared with s-GECSs for patients with stage C2 or C3 CVD. Although both c-GECSs and s-GECSs effectively reduced CV, the superior fit and comfort of c-GECSs improved patient compliance. Hence, c-GECSs are a viable alternative for patients who have difficulty tolerating s-GECSs.